Analisis Pendahuluan Pengembangan Lembar Kerja Peserta Didik Berbasis Realistic Mathematics Education Pada Materi Bangun Ruang Sisi Datar Kelas VIII MTsN 1 Solok - Rice Riyan Micola; Adevi Murni Adel; Reno Warni Pratiwi (Algebra: Journal of Matematics, Statistics and Computation, 2024)
Based on observations and interviews at school, the information obtained in learning activities has not used Learner Worksheets (LKPD), which are related to everyday life. This study analyzes the importance of developing Realistic Mathematics Education (RME) based LKPDs on learning Flat Side Spaces in class VIII MTsN 1 Solok. This type of research is development research with the Plomp model. The Plomp model has three phases: preliminary research, prototyping, and assessment. This research is at the preliminary research stage, namely preliminary analysis in the form of needs analysis, curriculum analysis, analysis of learner characteristics, concept analysis, and literature review analysis. Data is generated from observations and interviews with educators and students. From the analysis of the need to develop RME-based LKPD based on learning about flat-side space buildings materials.